1998
DOI: 10.1093/ije/27.4.561
|View full text |Cite
|
Sign up to set email alerts
|

Lung and kidney cancer mortality associated with arsenic in drinking water in Cordoba, Argentina

Abstract: The results add to the evidence that arsenic ingestion increases the risk of lung and kidney cancers. In this study, the association between arsenic and mortality from liver and skin cancers was not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
0
6

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(197 citation statements)
references
References 24 publications
6
185
0
6
Order By: Relevance
“…iAs is classified as a human carcinogen (IARC, 1987). Numerous epidemiologic studies have associated chronic exposure to iAs with increased prevalence of cancers of the skin, bladder, liver, lung, and stomach (Bates et al, 1995;Bates et al, 1992;Chen et al, 1992;Chen et al, 1985;Chiang et al, 1988;Chiou et al, 1995;Guo et al, 1997;Hopenhayn-Rich et al, 1996;Hopenhayn-Rich et al, 1998;Lewis et al, 1999;Smith et al, 1998;Smith et al, 1992;Tseng et al, 1968;Tsuda et al, 1995;Wu et al, 1989). Previous research of the effects of chronic exposure to iAs has focused primarily on its carcinogenic potential.…”
Section: Introductionmentioning
confidence: 99%
“…iAs is classified as a human carcinogen (IARC, 1987). Numerous epidemiologic studies have associated chronic exposure to iAs with increased prevalence of cancers of the skin, bladder, liver, lung, and stomach (Bates et al, 1995;Bates et al, 1992;Chen et al, 1992;Chen et al, 1985;Chiang et al, 1988;Chiou et al, 1995;Guo et al, 1997;Hopenhayn-Rich et al, 1996;Hopenhayn-Rich et al, 1998;Lewis et al, 1999;Smith et al, 1998;Smith et al, 1992;Tseng et al, 1968;Tsuda et al, 1995;Wu et al, 1989). Previous research of the effects of chronic exposure to iAs has focused primarily on its carcinogenic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, this area is banned and normally no one aware will eat clams collected from there. Contamination of mussels, seafood, and bivalves by toxic metals is frequently reported worldwide these last years in the range of 0.04-4.9 lg/g for Cd, 0.1-0.4 lg/g for Pb, 8-235 lg/g for Cu, and 0.15-0.75 lg/g for Cr (Hopenhayn-Rich et al, 1998;Saavedra et al, 2004;Bebianno et al, 2004;Romeo et al, 2006). Concentrations of heavy metal detected here are clearly higher than the one detected in mussels from the south part of France this last decade for Cd, that is 0.83 lg/g dried weight versus 1.08 lg/g of wet flesh weight, corresponding approximately to 5.4 lg/g of dried weight (Traoré et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The seafood production area of Boughrara, Tunisia, was banned a year ago because of pollution by heavy metals. Potential sources of toxic metal include groundwater contamination, metal working, leather tanning, and mining (Steenland et al, 1996;Hopenhayn-Rich et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Study on the SMR with As exposure from ground water in Argentina revealed dose-related association between As exposure and risk of kidney and lung cancers (Hopenhayn-Rich et al, 1998). The classification for exposure groups was based on estimated As concentration in drinking water such that less than 0.04 mg/L was designated the low group and over than 0.178 mg/L the high group.…”
Section: Internal Malignanciesmentioning
confidence: 99%